Model Based Dispatch Optimisation for Residential Districts – Analysing the Integration of Electricity Storage Systems and their Environmental Impact - Lewerenz, Steffen (Journal of Strategic Innovation and Sustainability, 2019)
In the European Union, residential districts consume a significant share of the total electricity, which is still mainly generated by conventional power plants. Consequently, utilising renewable energy carriers combined with electricity storage systems are necessary to mitigate climate change. To assess the electricity generation and the storage operation a techno-economic bottom-up model is applied and combined with a Life Cycle Assessment to evaluate the environmental impacts of the applied electricity storage system. Under the taken assumptions electricity storage systems have the potential to increase the degree of self-supply and autarky of the energy system as far as their prices decrease.